STUDI LITERATUR HUBUNGAN TINGKAT PENGETAHUAN DIET DIABETES DAN KEPATUHAN DIET PENDERITA DIABETES MELITUS TIPE 2 - Ni Wayan Sri Santika Dewi; Gusti Ayu Dewi Kusumayanti; I Wayan Juniarsana (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2022)
Non-Communicable Diseases (PTM) is still a regional and national health problem. One of the PTM that has the highest number is Diabetes Militus. Nutritional status and blood glucose levels are closely related to diabetes mellitus. The purpose of the literature review is to find out the nutritional status and blood glucose levels in patients with diabetes mellitus in Wangaya District Hospital, Denpasar. The literature review design is a case study that illustrates the nutritional status and blood glucose levels of patients with diabetes mellitus. Subjects in the study were 2 patients. The nutritional status of diabetes mellitus patients is related to the blood glucose levels of diabetes mellitus patients where the higher the nutritional status, the higher or worse the blood glucose level.Keywords: diabetes mellitus, nutritional status, blood glucose levels.